A Comparison of Drug Delivery Systems of Zr‐Based MOFs and Halloysite Nanotubes: Evaluation of β‐Estradiol Encapsulation. Issue 31 (16th August 2019) - Luo, Ting; Liu, Hao; Liang, Yong; Tang, Jun; Zhou, Jinrong; Liang, Wenjie; Cai, Jianfeng; Xu, Hai
Abstract: The low cytotoxic Zr‐based MOF PCN‐221, which exhibited the ability to entrap β‐estradiol model drug, was studied as a drug delivery system. As a comparison, another drug carrier, halloysite nanotubes, was also investigated. Both PCN‐221 and halloysite nanotubes were characterized by IR spectroscopy, powder X‐ray diffraction (PXRD), and transmission electron microscopy (TEM). β‐estradiol was loaded mainly on skeleton and partially on the external surface of PCN‐221. We show that controlled release of β‐estradiol from PCN‐221 was observed over more than 31 days, compared with the 20 days release period from halloysite nanotubes, indicating PCN‐221 are a superior carriers of β‐estradiol. Abstract : A low cytotoxic metal–organic framework (MOF) constructed from [Zr8 O6 (CO2 )12 ] 8+ cluster and 5, 10, 15, 20‐tetrakis(4‐carboxyphenyl)porphyrin ligands, PCN‐221 was investigated as a drug carrier. β‐estradiol was chosen as the model drug molecule which was absorbed into inner pores and channels of PCN‐221 by diffusion. PCN‐221 showed high drug loading and sustained release in PBS buffer solutions (pH=7.4 and 37 °C).